PENGARUH INDEKS PEMBANGUNAN MANUSIA DAN PENGANGGURAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DI PROVINSI SULAWESI SELATAN - safitri, Ulfa Wardani (Institut Agama Islam Negeri (IAIN) Bone, 2023)
The purpose of this research was to determine the effect of human development index (HDI)and unemployment on gross regional gross domestic product (GRDP) in South Sulawesi Province for the period of 2010 - 2019. This research used quantitative research. The source of data used in this research was secondary data, that is time series and obtained from the official website of the Central Statistics Agency of South Sulawesi Province The data collection technique used is the documentation technique. The data analysis technique uses multiple linear regression analysis model which is supported by classical assumption test and hypothesis test.The result showed that the human development index has a positive and significant effect on the gross regional domestic product (GRDP) in South Sulawesi Province for the 2010-2019 period. Human development made a relatively large contribution to increasing productivity. When the human development index rises, the gross regional domestic product (GRDP) in South Sulawesi Province will increase. Meanwhile, unemployment has a negative effect on the gross regional domestic product (GRDP) in South Sulawesi Province for the 2010-2019 period. When unemployment rises, the gross regional domestic product (GRDP) in South Sulawesi Province will decrease